Evaluasi Usability dan User Experience E-Commerce Menggunakan Cognitive Walkthrough (CW) dan User Experience Questionnaire (EQ) - Meinarini Catur Utami; Qurrotul Aini; Moch Choiril Anwar; Rika Novita Wardhani; Winda Wulandari (Jurnal Ilmiah Matrik, 2026)
The rapid growth of e-commerce demands user-friendly interfaces to ensure optimal user experience. Application X still exhibits usability issues, including ineffective search functionality, difficulty accessing customer service, and unintuitive navigation, indicating that the interface does not adequately support ease of use. This study aims to analyze the evaluation of usability and user experience on mobile e-commerce applications by integrating Cognitive Walkthrough (CW) and User Experience Questionnaire (UEQ). CW was used to identify usability issues through task-based scenarios, while UEQ measured user perceptions across six dimensions: attractiveness, clarity, efficiency, reliability, stimulation, and novelty. Data were collected from 20 respondents using purposive sampling. The results reveal task errors and failures, reflecting low efficiency and usability. UEQ findings indicate that clarity and stimulation are above average, while efficiency, novelty, reliability, and attractiveness remain low. These results confirm that poor usability significantly degrades user experience, highlighting the need for interface design improvements.